2010
DOI: 10.1063/1.3475500
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional electron gases in polycrystalline MgZnO/ZnO heterostructures grown by rf-sputtering process

Abstract: This paper reports the formation of two-dimensional electron gas ͑2DEG͒ in rf-sputtered defective polycrystalline MgZnO/ZnO heterostructure via the screening of grain boundary potential by polarization-induced charges. As the MgZnO thickness increases, the sheet resistance reduces rapidly and then saturates. The enhancement of the interfacial polarization effect becomes stronger, corresponding to a larger amount of resistance reduction, when the Mg content in the cap layer increases. Monte Carlo method by incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 31 publications
8
42
0
Order By: Relevance
“…The physical distance between this plane of a high carrier density and the gate dielectric surface is expected to suppress both long‐range Coulomb scattering by trapped charges and short‐range scattering from dielectric surface topological imperfections and chemical defects. The term 2DEG is used here since charge conduction in these homojunctions is still ideal as seen in phonon‐limited ZnMgO/ZnO heterojunctions grown by molecular beam epitaxy (MBE) and in the temperature‐independent regime as seen in sputtered ZnMgO/ZnO heterojunctions . Further optimization of film solution‐processing and dopant chemistry would likely improve the performance further.…”
Section: Performance Metrics Of the Indicated Tft Devices On Si/sio2 mentioning
confidence: 99%
“…The physical distance between this plane of a high carrier density and the gate dielectric surface is expected to suppress both long‐range Coulomb scattering by trapped charges and short‐range scattering from dielectric surface topological imperfections and chemical defects. The term 2DEG is used here since charge conduction in these homojunctions is still ideal as seen in phonon‐limited ZnMgO/ZnO heterojunctions grown by molecular beam epitaxy (MBE) and in the temperature‐independent regime as seen in sputtered ZnMgO/ZnO heterojunctions . Further optimization of film solution‐processing and dopant chemistry would likely improve the performance further.…”
Section: Performance Metrics Of the Indicated Tft Devices On Si/sio2 mentioning
confidence: 99%
“…For optimal interface quality, epitaxial material growth is commonly carried out via MBE or pulsed laser deposition on single-crystal substrates, such as sapphire or ScAlMgO 4 ( 33 , 37 ). However, it was shown that 2DEG could also form in ZnO/ZnMgO heterointerfaces grown on glass substrates via less elaborate techniques, such as RF sputtering ( 36 ). Despite their polycrystalline nature, the heterointerfaces exhibited enhanced sheet electron concentration and mobility with a characteristic temperature-independent behavior ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that 2DEG could also form in ZnO/ZnMgO heterointerfaces grown on glass substrates via less elaborate techniques, such as RF sputtering ( 36 ). Despite their polycrystalline nature, the heterointerfaces exhibited enhanced sheet electron concentration and mobility with a characteristic temperature-independent behavior ( 36 ). …”
Section: Introductionmentioning
confidence: 99%
“…A 2DEG formed at the interface has also been reported using ZnO/ZnMgO (Ref. 41) interfaces and bilayered In 2 O 3 -ZnO TFTs processed form solution can now achieve over 45 cm 2 V À1 s À1 mobility. 42 These trap sites often cause shifts in threshold voltage and affect leakage characteristics.…”
Section: Introductionmentioning
confidence: 66%